A collaborative programme in sustainability and social responsibility (2016)
Purpose: The purpose of this paper is to collect methodological strategies used in the training of future teachers to develop competences in sustainability and social responsibility (SSR). The proposal in this paper is to show how students learn and develop competences by performing practical activities and through a collaborative experience, conducted in a real-life context in the university campus. Design/methodology/approach: This paper collects together a selection of competences and sub-competences in SSR, together with the methodological scenarios that allowed their implementation. The results in the acquisition of competences, as well as the efficiency of the methodological strategies employed, were obtained from the qualitative analysis of student questionnaires and of their final academic results. Findings: Changing the teaching methods to include collaborative methodological strategies facilitates the acquisition of SSR competences. Research limitations/implications: A methodological limitation of this study is the fact that it has taken place in one academic year. The authors realize that to provide evidence of a profound behavioural change (which goes beyond the improvement of a habit), there is a need to carry out a longer study, which is complex when working with final year students. The authors are suggesting that the University carry out prolonged studies on the implementation and assessment of competences in SSR in the University and afterwards in the work place. Practical implications: At the start of the course year, a problem was identified, namely, that future teachers lacked sustainable habit patterns. This was turned into a learning opportunity that led to a collaborative SSR programme on the campus. Social implications: Creating varied practical methodological scenarios has contributed to the development of SSR competences by the pupils. Students have questioned their lifestyles and have modified their consumption habits. Additionally, doing a transdisciplinary collaborative programme in our own campus has played a part in changing our organization for the better and has facilitated combining research and teaching. Originality/value: This paper helps clarify how SSR competences can be developed in a local, real-life context. © 2016, © Emerald Group Publishing Limited.